Deficiency of eNOS exacerbates early-stage NAFLD pathogenesis by changing the fat distribution. Issue 1 (December 2015) - Nozaki, Yuichi; Fujita, Koji; Wada, Koichiro; Yoneda, Masato; Shinohara, Yoshiyasu; Imajo, Kento; Ogawa, Yuji; Kessoku, Takaomi; Nakamuta, Makoto; Saito, Satoru; Masaki, Naohiko; Nagashima, Yoji; et al.
Abstract Background Although many factors and molecules that are closely associated with non-alcoholic fatty liver disease (NAFLD)/non-alcoholic steatohepatitis (NASH) have been reported, the role of endothelial nitric oxide synthase (eNOS)-derived nitric oxide (NO) in the pathogenesis of NAFLD/NASH remains unclear. We therefore investigated the role of eNOS-derived NO in NAFLD pathogenesis using systemiceNOS -knockout mice fed a high-fat diet. Methods eNOS -knockout and wild-type mice were fed a basal diet or a high-fat diet for 12 weeks. Lipid accumulation and inflammation were evaluated in the liver, and various factors that are closely associated with NAFLD/NASH and hepatic tissue blood flow were analyzed. Results Lipid accumulation and inflammation were more extensive in the liver and lipid accumulation was less extensive in the visceral fat tissue ineNOS -knockout mice, compared with wild-type mice, after 12 weeks of being fed a high-fat diet. While systemic insulin resistance was comparable between theeNOS -knockout and wild-type mice fed a high-fat diet, hepatic tissue blood flow was significantly suppressed in theeNOS -knockout mice, compared with the wild-type mice, in mice fed a high-fat diet. The microsomal triglyceride transfer protein activity was down-regulated ineNOS -knockout mice, compared with wild-type mice, in mice fed a high-fat diet. Conclusions A deficiency of eNOS-derived NO may exacerbate the early-stage of NASH pathogenesis by changing the fat distribution in a mouse model via the regulation of hepatic tissue blood flow.